Microsoft 2.0 : - Foley, Mary Jo (John Wiley & Sons, 2008)
Presents an analysis of Microsoft’s future without Bill Gates, evaluating the prospects of the company keeping up with technological innovations and remaining a market leader against an increasing number of competitors